2008
DOI: 10.1108/13527590810860203
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of the results of continuous improvement in an industrial company

Abstract: Purpose -The purpose of this paper is to show a real experience of how a scheme of continuous improvement has been gradually transformed, from a very unsuccessful start, passing through different phases and finally delivering results for the firm. Design/methodology/approach -The authors analyse the evolution of the formal programs of continuous improvement of a firm in a traditional sector (food). The data for the research were gathered by means of participatory observation over the course of 18 months spent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 31 publications
2
47
0
8
Order By: Relevance
“…For the implementation of QCCs, previous research has suggested that their successful implementations are based on few factors (Miina, 2012;Seyedhosseini et al, 2011), including the number of ideas have been submitted (Karlsson & Ahlstrom, 1996), implemented (Baides & Moyano-Fuentes, 2012;Winfield, 1994), and the time improvement participants spent in developing ideas (Marin-Garcia et al, 2008). This study followed Ma et al (2014) that the number of QCC meetings is a proxy to measure the quantity of QCCs, whilst the number of completed and presented QCCs is a proxy for quality of QCCs.…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…For the implementation of QCCs, previous research has suggested that their successful implementations are based on few factors (Miina, 2012;Seyedhosseini et al, 2011), including the number of ideas have been submitted (Karlsson & Ahlstrom, 1996), implemented (Baides & Moyano-Fuentes, 2012;Winfield, 1994), and the time improvement participants spent in developing ideas (Marin-Garcia et al, 2008). This study followed Ma et al (2014) that the number of QCC meetings is a proxy to measure the quantity of QCCs, whilst the number of completed and presented QCCs is a proxy for quality of QCCs.…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…Its disclosure took place in Brazil in the late 1980s and early 1990s, when the first concepts of quality emerged according to the Japanese model. There are several books (Toledo, 1986;Imai, 1997;Kume, 1993) and articles on this topic, which relate the use of these techniques to continuous improvement (Marin-Garcia et al, 2008;Oprime et al, 2010) and the effects of these activities on productivity (Bessant & Caffyn, 1997;Savolainen, 1999;Harrison, 2000;Bessant et al, 2001;Delbridge & Barton, 2002;Hyland et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…(Eisenhardt, 1989;Yin, 1993). El caso de estudio es bastante utilizado en el área de gestión de empresas o mejora continua (Abdulmalek y Rajgopal, 2007; García-Arca y PradoPrado, 2008;Marin-Garcia et al, 2008;Prado Prado, 1998;Scoggin et al, 2003;Vazquez-Bustelo y Avella, 2006). Pero se descarta el caso de estudio para esta tesis ya que al tener como objetivo realizar un estudio sobre la evolución de la mejora continua, llevaría a plantear un estudio de mucha duración y esfuerzo, sin tener ninguna certeza de que las empresas van a conseguir evolucionar hasta etapas avanzadas.…”
Section: Metodologías Cualitativasunclassified
“…Entre las herramientas de trabajo en grupo se encuentran los círculos de calidad, los grupos multifuncionales o los equipos de mejora de una duración predeterminada (GarciaLorenzo y Grütter et al, 2002;Kerrin y Oliver, 2002;MarinGarcia et al, 2008a;Rapp y Eklund, 2002;Sillince et al, 1996). Por otra parte, se pueden utilizar sistemas de sugerencias individuales Rapp y Eklund, 2002;Schuring y Luijten, 2001;Sillince et al, 1996), aunque sólo se obtienen resultados comparables a las mejoras de grupos si son excepcionalmente bien gestionados (Marin-Garcia et al, 2008b;Rapp y Eklund, 2002).…”
Section: Jj Garcia-sabater Ja Marin-garciaunclassified
See 1 more Smart Citation